Impact of individualized pain plan on the emergency management of children with sickle cell disease. Issue 10 (24th June 2014) - Krishnamurti, Lakshmanan; Smith‐Packard, Bethanny; Gupta, Ashish; Campbell, Mary; Gunawardena, Sriya; Saladino, Richard
<x xml:space="preserve">Abstract</x> Background Vaso‐occlusive crisis (VOC) the hallmark of sickle cell disease (SCD) is often treated inadequately in the emergency department (ED). We hypothesized that pain management plans individualized for each patient can improve pain management and lead to high levels of patient satisfaction. Procedure Starting in 2002, we treated all patients with SCD reporting to Children's Hospital of Pittsburgh (CHP) ED with VOC using a structured algorithm. We recorded regimens used successfully for each patient as an "individualized pain plan" and implemented it during subsequent VOC visits and adjusted it to patient response. We compared rates of hospitalization following an ED visit with VOC and readmission within 1 week after discharge for CHP with that of four comparable hospitals from Pediatric Health Information (PHIS) database. Patients and parents completed surveys of satisfaction with pain management and with care. Results Between 2002 and 2008 there was a greater decline in the rate of admission of patients presenting to the ED at CHP (78% to 52%) as compared to PHIS (71% to 68%), (P < 0.05) and readmission rates at CHP (7.3% to 3.2%) as compared to PHIS (6.5% to 5.1%) (P < 0.05). Improvement in pain score during ED management was 2.0 or more on a Wong Baker scale of 0–5 (P < 0.01). Participants on average, rated quality of pain management as very good or higher. Conclusion Individualized pain management plans in the ED are effective in delivering high quality management of VOC and are associated with a high level of patient satisfaction and decreased avoidable hospitalizations. Pediatr Blood Cancer 2014; 61:1747–1753. © 2014 Wiley Periodicals, Inc.